(untitled) (Ameghiniana, 2014)
The palynological analysis is used to reconstruct the paleoenvironment and the prevailing clima tic regime during the deposition of the Pedro Luro Formation in the Colorado Basin. On the basis of its palynomorphs, foraminifera and nannoplankton, the studied levels are referred to the Danian. Comparison of fossil genera with extant taxa allowed recognition of several paleocommunities, namely near-shore, marsh, lacustrine, steppe, montane forest, cloudy forest, transitional forest. Taking into account the present clima tic distribution of the extant vegetal families recognized, the paleoclimatic conditions during the deposition of the Pedro Luro Formation were warm and humid. The marine palynomorphs indicate that the Pedro Luro Formation was deposited at different distances from the terrigeneus influx.